2022
DOI: 10.3390/v14102215
|View full text |Cite
|
Sign up to set email alerts
|

Viral Small Terminase: A Divergent Structural Framework for a Conserved Biological Function

Abstract: The genome packaging motor of bacteriophages and herpesviruses is built by two terminase subunits, known as large (TerL) and small (TerS), both essential for viral genome packaging. TerL structure, composition, and assembly to an empty capsid, as well as the mechanisms of ATP-dependent DNA packaging, have been studied in depth, shedding light on the chemo-mechanical coupling between ATP hydrolysis and DNA translocation. Instead, significantly less is known about the small terminase subunit, TerS, which is disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 120 publications
0
13
0
Order By: Relevance
“…Perhaps GpsA and GpsB function together or separately as a PLE-specific TerS (Figure 6C). In line with this prediction, bioinformatic analysis hints that GpsB may have a DNA-binding motif, a feature expected of TerS proteins (31). Alternatively, GpsA and/or GpsB could modulate Gpi’s binding to TerL, selectively removing Gpi to allow ICP1’s TerS to package PLE genomes (Figure 6C).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Perhaps GpsA and GpsB function together or separately as a PLE-specific TerS (Figure 6C). In line with this prediction, bioinformatic analysis hints that GpsB may have a DNA-binding motif, a feature expected of TerS proteins (31). Alternatively, GpsA and/or GpsB could modulate Gpi’s binding to TerL, selectively removing Gpi to allow ICP1’s TerS to package PLE genomes (Figure 6C).…”
Section: Discussionmentioning
confidence: 82%
“…Satellites interfere with late gene expression (18,32,50), inhibit phage-sized capsid assembly (12,(51)(52)(53), and interfere with genome packaging (7)(8)(9). Interestingly, despite the notable structural dissimilarity of TerSs (31), other phage satellites target phage TerSs. In fact, this variable target can limit the satellites' ability to interfere with other phages (8).…”
Section: Data Availabilitymentioning
confidence: 99%
“…PhageTerm analysis for the genome ends detected long direct terminal repeats (2298 bp). All three phage genomes were dsDNA ( Figure 5 ), which were confirmed by cutting with restriction endonucleases, and included ORFs encoding small and large terminase subunits, which are hallmark genes for tailed dsDNA bacteriophages that package their genomes into a preformed procapsid [ 29 , 30 ]. Although Lumi is a unique phage, ORF searches with Blastp suggested that Lumi shares some similar ORFs with the Achromobacter phage JWF, a siphovirus originating from sewage [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…An interaction with gp17 through its C-terminal domain would lead to the formation of TerS-TerL complex that then proceeds with DNA cleavage and insertion of DNA end into the portal channel to initiate packaging. Though models have been proposed in which DNA passes through the TerS channel and may even be threaded during DNA translocation, the evidence is not consistent with such models [ 88 , 89 ]. Mutations of residues that line the channel, including partial or complete deletion of one of the channel helices, do not lead to loss of DNA binding in vitro or cause lethality in vivo.…”
Section: Genome Packagingmentioning
confidence: 99%